2015
DOI: 10.3329/bjp.v10i1.21462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crude saponins from <i>Gaultheria trichophylla</i> extract on growth inhibition in human colorectal cancer cells

Abstract: Research ArticleEffect of crude saponins from Effect of crude saponins from Effect of crude saponins from Gaul-GaulGaultheria trichophylla theria trichophylla theria trichophylla extract on extract on extract on growth inhibition in human colorecgrowth inhibition in human colorecgrowth inhibition in human colorectal cancer cells tal cancer cells tal cancer cells BJP IntroductionColorectal cancer is the third most common malignant neoplasm worldwide and has become one of the major causes of cancer mortality (Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The plants of genus Gaultheria have been reported to suppress the malignant neoplastic cells (Li et al, 2010). Our previous study also showed that the crude saponins caused the inhibition of colon cancer cells lines through mechanism involving apoptosis (Alam et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The plants of genus Gaultheria have been reported to suppress the malignant neoplastic cells (Li et al, 2010). Our previous study also showed that the crude saponins caused the inhibition of colon cancer cells lines through mechanism involving apoptosis (Alam et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the material was washed three times with PBS, then keep in 4 °C. The cells were photographed by using a fluoresence microscope (Dino-Lite, Hsinchu, Taiwan) (Alam et al, 2015).…”
Section: Dna Condensation Assaymentioning
confidence: 99%